Генезис тероризму - Васильків, Ф.Ф. (Держава і право, 2012)
Здійснено історико-правове дослідження витоків тероризму та аналіз поняття «тероризм». Осуществлены историко-правовое исследование истоков терроризма и анализ понятия «терроризм». This paper addresses the historical and legal study of the origins of terrorism and the analysis of the concept of "terrorism".